Production and Supply Chain of Shellfish (Mollusca) as a Strategy to Strengthen Sustainable Fisheries Agribusiness in Sidoarjo, East Java (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
The purpose of this study was to find out about the marketing chain of shellfish commodities in Sidoarjo. This study was conducted using survey methods, and data analysis was conducted using descriptive methods, marketing margins, and the fisherman’s share. The results of the study show that the process of catching was carried out by using dredges. The type of shellfish caught are the short-necked clam (Paratapes undulatus) and the Blood cockles (Anadara granosa and Anadara antiquta). Daily production from fishermen averages 80-100 kg/day and is dominated by blood cockles. The process of shellfish marketing is carried out by fishermen to collectors and is marketed directly to buyers. The collectors will market the shells to retailers and to restaurants. The results of this research obtained 3 types of marketing channels, namely types A, B, and C. The shortest channel types A, namely from fishermen directly to consumers, followed by type B from fishermen to collectors, retailers, and finally to consumers. While type C is the most extended marketing channel, starting from fishermen, collectors, restaurants, and the last is consumers. Type A is an effective marketing channel and efficient for fishermen because it can be obtained from them as compared to other types, and has the fisherman’s share of 42.86%.